Relevansi Pemahaman Materi Saling Menasehati terhadap Sikap Peduli Sosial Siswa dalam Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Atas Cendana Pekanbaru - Miftahir Rizqa; Anisa Fitri; Risnawati (FKIP, Universitas Palangka Raya, 2025)
This article discusses the influence of mutual understanding of material counseling on attitudes of social concern in the learning of Islamic religion education in high schools in Cendana Pekanbaru. This type of research is quantitative research on correlation forms. Sampling in this study used the simple random sampling technique, so we found samples of a total of 24 people. Data collection techniques are observation, documentation, and lifting. Technical data analysis using the product moment technique found that the known value of R count is 0.027. While the R table known is 0.413, So it is known that 0.027 < 0.413, which means there is no significant relationship between the understanding of material mutually advised and the social concerns of the pupils at Cendana Pekanbaru High School. Although the absence of influence between understandings of the material is mutually advised on the social interests of pupils, the excellent social care attitude that exists in pupils who attend Candana High School must be caused by various other factors. To list the various factors that must be considered when conducting additional research.